The Effectiveness of Eco Enzymes to Suppress the Development of Sarcoptes scabiei Mites in Goat In Vivo - Dzakwan Naufal; Nurzainah Ginting; Peni Patriani; Anwar (Jurnal Peternakan Integratif, 2024)
Scabies is a disease caused by the Sarcoptes scabiei mite that attacks goats. It is quite difficult for traditional goat farmers to get scabies medicine because the price is expensive so alternative treatment is needed. The purpose of this study was to determine the effectiveness of eco enzymes in suppressing the growth of Sarcoptes scabiei mites in vivo. This study has 5 treatments. P0 (Sulfidex 100ml), P1 (Aquades 100ml), K1 (25% eco enzyme + 75% aquades), K2 (50% eco enzyme + 50% aquades), K3 (75% eco enzyme + 25% aquades). Goat samples used were 5 heads in each sample. The parameters observed were alopecia, thickening, and scab. The results of the study on the parameters of alopecia, thickening, and scab. The use of ekoemzim at a dose of 75% was able to balance the provision of sulfadex on the parameters of alopecia, and scab. In the thickening parameter, the provision of eco enzyme at a dose of 75% is better than the provision of 100 ml sulfadex. In conclusion eco enzyme as a scabicide solution with a dose of 75% is considered capable of suppressing the growth of Sarcoptes scabiei, as well as being able to balance the administration of sulfadex on alopecia and scab parameters.